Neuroticism and Celebrity Worship Among NCT Boy Group Fans (NCTzen): A Psychological Exploration - Larashanty, Sefiana; Merida, Sarita Candra (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to determine the influence between neuroticism on celebrity worship in fans of the NCT boy group (NCTzen). This research uses quantitative methods with simple linear regression methods. The subjects in this study were adolescents to early adults aged 14 to 25 years who were fans of the NCT boy group who lived in Bekasi City with the sampling technique, namely non-probability sampling using purposive sampling method. The participants in this study totaled 172 people. The data collection technique used a Likert scale. The results of this study found an influence between neuroticism personality on celebrity worship with a significance (p) of 0.001 (p <0.05) which means (Ha) is accepted and (Ho) is rejected. The correlation value obtained is 0.793 and shows a strong relationship but the categorization test results get the results of neuroticism at a moderate level and celebrity worship at a low level.